DIFFERENTIATED INSTRUCTION IN INCLUSIVE EFL CLASSROOMS: A TWO-CYCLE CASE STUDY FROM INDONESIA - Susilawati; Fitri Aprianti; Eline Rozaliya Winarto (University of Kuningan, 2026)
The implementation of inclusive classrooms is a mandated educational policy in Indonesia, requiring schools to accommodate students with diverse learning needs, including those with special educational needs (SEN). Within this framework, this study investigates how differentiated instruction (DI) is enacted in an inclusive junior high school EFL classroom in Cirebon and examines its influence on students’ academic engagement and affective experiences. This study provides the first systematic documentation of all four DI components, including content, process, product, and learning environment, across two instructional cycles in an Indonesian inclusive EFL classroom, with disaggregated analysis of student responses by learning profile. Adopting a qualitative case study design, data were collected through classroom observations, formative assessments, teacher reflections, and semi structured interviews, enabling methodological triangulation across the two cycles. The findings show that the teacher implemented multiple forms of differentiation, particularly in content and process, through strategies such as recorded word lists, peer assisted learning, group discussions, visual scaffolds, and tiered tasks. As instruction progressed, these strategies were refined to respond more consistently to students’ diverse readiness levels and learning challenges. Student experiences varied by learning profile: auditory learners showed strong academic engagement but limited affective involvement; kinesthetic learners demonstrated balanced participation; and verbal social learners benefited most from collaborative activities. Students with SEN were supported through extended time, visual aids, and peer mentoring, while independent learners responded positively to opportunities for creative autonomy. Overall, the study shows that differentiated instruction enhances equitable access to EFL learning while fostering motivation, confidence, and belonging in heterogeneous classrooms..